Malaria situation in a clear area of Iran: an approach for the better understanding of the health service providers’ readiness and challenges for malaria elimination in clear areas - Hosein Azizi; Elham Davtalab-Esmaeili; Mostafa Farahbakhsh; Maryam Zeinolabedini; Yagoub Mirzaei; Mohammad Mirzapour (Malaria Journal, 2020)
Abstract Background Malaria mortality and morbidity have decreased in recent years. Malaria elimination (ME) and effective efforts to achieve ME is one of the most important priorities for health systems in countries in the elimination phase. In very low transmission areas, the ME programme is faced with serious challenges. This study aimed to assess the trend while getting a better understanding of Health Service Providers’ (HSPs) readiness and challenges for ME in a clear area of Iran. Methods This study was performed in two phases. At first, the malaria trend in East Azerbaijan Province, was surveyed from 2001 to 2018; afterward, it was compared with the national situation for a better understanding of the second phase of the study. Data were collected from the Ministry of Health’s protocol and the health centre of the province. In the second phase, malaria control programme experts, health system researchers, and health managers’ opinions were collected via in-depth interviews. They were asked regarding HSPs readiness and appropriate Malaria Case Management (MCM) in a clear area and possible challenges. Results A total of 135 and 154,560 cases were reported in the last 18 years in East Azerbaijan Province and Iran, respectively. The incidence rate decreased in East Azerbaijan Province from 0.4/10,000 in 2001 to zero in 2018. Furthermore, no indigenous transmission was reported for 14 years. Also, for the first time, there was no indigenous transmission in Iran in 2018. The main elicited themes of HSPs readiness through in-depth interviews were: appropriate MCM, holistic and role-playing studies for assessment of HSPs performance, system mobilization, improving identification and diagnosis of suspected cases in the first line. Similarly, the main possible challenges were found to be decreasing health system sensitivity, malaria re-introduction, and withdrawing febrile suspected cases from the surveillance chain. Conclusion Health systems in eliminating phase should be aware that the absence of malaria cases reported does not necessarily mean that malaria is eliminated; in order to obtain valid data and to determine whether it is eliminated, holistic and role-playing studies are required. Increasing system sensitivity and mobilization are deemed important to achieve ME.